Prevalence and characteristics of asthma in the aquatic disciplines - Montjoy, M.; Fitch, K.; Boulet, L.-P.; Bougault, V.; van Mechelen, W.; Verhagen, E. (The Journal of Allergy and Clinical Immunology, 2015)
Background Despite the health benefits of swimming as a form of exercise, evidence exists that both the swimming pool environment and endurance exercise are etiologic factors in the development of asthma. The prevalence of asthma in swimmers is high compared with that in participants in other Olympic sport disciplines. There are no publications comparing the prevalence of asthma in the 5 aquatic disciplines.